When Ratings Move, Do Financials Follow? : ESG Ratings and Their Impact on EU Companies’ Financial Performance and Valuation - Ghasemi, Bardia (2025)
In recent years, new directives and policies have been implemented in the European Union regarding ESG issues. From a sustainability point of view, these changes combined with the aim of guiding companies to more sustainable long-term operations. However, from the business point of view, the other argument in this regard is whether these mandatory compliances can generate more money as well. So far, there has been extensive research targeting different areas related to this field presenting conflicting findings about regulatory frameworks, the role of ESG rating agencies, the financial performance of the companies, and investor’s trust in sustainable initiatives. While most of the studies lean towards the benefits of the higher ESG ratings on the financial well-being of the companies, others argue that factors such as higher short-term cost of compliance, unorganized methods of disclosures, and the subjectivity of the ratings provided by the agencies might mislead investors. Recognizing these discrepancies, this thesis aims to shed light exclusively on the firm valuation and the financial performance of the European Union companies measuring the extent of the effect that ESG ratings have on the liquidity level, stock prices, ROA, ROE, and leverage using a five-year panel-regression model. The findings conclude that although higher ESG ratings might have a more positive effect on the small firms, the large and medium firms lag when it comes to returns on the higher ratings mainly due to the cost of compliance, materiality of the initiatives, higher transparency and lower information asymmetry.